Fish development and genetics : (World Scientific Pub., 2004)
The zebrafish is the most important fish model in developmental and genetic analyses. This book contains 19 review articles covering a broad spectrum of topics, from development to genetic tools. The contents range from early development, the role of maternal factors and gastrulation, to tissue differentiation and organogenesis, such as development of the organizer, notochord, floor plate, nervous system, somites, muscle, skeleton and endoderm. The genetic tools cover morpholino knock-down, transgenics, fish cloning, transposons and genome evolution. The book also includes two chapters on genome mapping and embryonic stem cells in medaka, another important model fish. Summarizing the state-of-the-art studies of the zebrafish model and focusing on the molecular aspects of development, this book is a valuable reference for students learning the basic aspects of the zebrafish model, and for researchers seeking resources in zebrafish research.